Dinâmica socioespacial urbana de Cuité-PB resultante da implantação do campus de saúde e educação da UFCG - Gomes, Maria Verônica de Azevedo (2014)
This research addresses the complexity of the phenomena intra-urban the small brazilian city. The aim of this study was to analyze the social and spatial dynamics occurring in Cuité due to the presence of Centro de Educação e Saúde-CES Federal of Campina Grande-UFCG. The CES was installed in Cuité in the second half of the year of 2006 and triggered transformers processes in its socio and spatial arrangement, which prompted us to analyze them and understand them. To do so, proceed with the review of literature depicting the Brazilian Urban Geography, that based on building analyzes that seek to understand the differences and specificities of small Brazilian town texts. Added to this, the analysis of documents relating to the CES installation process, conducting interviews with key individuals involved in this process, the questionnaires to students and this institution servers and collecting data from the real estate companies and municipal administrative institutions. The findings from this research allow us to affirm that the presence of this CES comes attracting investment and people to Cuité, increasing production and real estate marketing and expanding its urban area.